PRETREATMENT OF KAOLIN INTO METAKAOLIN - REZKY I. ANUGRAH; SYAFEI S. RASJAD (Indonesian Mining Journal, 2010)
Most of metakaolin is used in portland cement industries as an additive to improve the compressive strength of the cement. Using Cicalengka and Bangka kaolin as metakaolin raw material, R & D Center for Mineral and Coal Technology found that Bangka kaolin was more suitable in metakaolin preparation because its initial Al2O3 content (32.80%) rises up to 37.50% after decantation, meanwhile Cicalengka one can not fulfill the requirements. The non-decanted Bangka kaolin (37.50% Al2O3) exceeds the Al2O3 content of metakaolin that has been produced commercially by Asian Ceratec Corporation. Calcination processing follows the decantation one. The decanted Bangka kaolin was then pelletized to have calcining burnt did well. The pellet was burnt in 1 x 0.5 m static laboratory furnace at some tempera- tures and holding times. Burning temperature of 9000 C and 20 minutes holding time showed common calcined kaolin characteristic; sheet-like structure, but at some parts it has developed into unregularly thicker sheet structure due to amorphous (non-reactive phase) formation. This phenomenon signs that recrystallization temperature has been achieved and many hydroxil ions has been lost.